Existence, uniqueness and HUR stability of fractional integral equations by random matrix control functions in MMB-space. Issue 1 (1st January 2021) - Chaharpashlou, Reza; Saadati, Reza; Abdeljawad, Thabet
Abstract : In this paper, we consider a generalized triangular norm on matrix and introduce Menger Banach matrix valued spaces. Next, we apply a class of random matrix control functions to investigate the existence, uniqueness and HUR stability of a class of fractional Volterra integral equations. We use the Radu-Mihe method, to get an approximation for the mentioned fractional Volterra integral equation.